Different influences on mitochondrial function, oxidative stress and cytotoxicity of antibiotics on primary human neuron and cell lines. Issue 4 (31st December 2018) - Xiao, Yao; Xiong, Ting; Meng, Xiangping; Yu, Danfang; Xiao, Zheng; Song, Lin
Abstract: Although antibiotics are generally well tolerated, their toxic effects on the central nervous system have been gained attention. In this study, we systematically investigated the neuron toxicity of antibiotics from six different classes. We show that clinically relevant concentrations of metronidazole, tigecycline, azithromycin and clindamycin but not ampicillin or sulfamethoxazole induce apoptosis of human primary neuron cells and lines. Notably, tigecycline, azithromycin and clindamycin cause neuron cell oxidative damage whereas metronidazole has no effect on reactive oxygen species (ROS) production, suggesting that metronidazole induces neuron death via ROS‐independent mechanism. Tigecycline, azithromycin and clindamycin induce mitochondrial dysfunctions via targeting different mitochondrial respiratory complexes, leading to mitochondrial membrane potential disruption and energy crisis. The deleterious effects of antibiotics are reversed by pretreatment of neuron cells with antioxidant. Our work highlights the different influences of antibiotics on mitochondrial dysfunction, oxidative damage and cytotoxicity in neuron cells. We also provide a strategy to prevent the neurotoxicity.